Transcription factor network dynamics during the commitment to oncogene-induced senescence - Vasilopoulos, Themistoklis; Martínez-Zamudio, Ricardo Iván (Frontiers in Epigenetics and Epigenomics, 2024)
Aberrant oncogenic signaling causes cells to transition into oncogene-induced senescence (OIS) to limit uncontrolled proliferation. Despite being a potent tumor suppressor mechanism, OIS is an unstable cell state susceptible to reprogramming that can promote tumorigenesis. Therefore, elucidating the underlying gene regulatory mechanisms that commit cells to OIS is critical to identifying actionable targets to modulate the senescence state. We previously showed that timely execution of the OIS program is governed by hierarchical transcription factor (TF). However, the gene regulatory mechanisms that prime cells to commit to the OIS fate early upon oncogene hyperactivation are currently not known. Here, we leveraged our time-resolved multi-omic profiling approach to generate TF networks during the first 24 hours of oncogenic HRASG12V activation. Using this approach, we demonstrate that the commitment to OIS requires the rearrangement of the TF network on a pre-established epigenomic landscape, priming the cells for the substantial chromatin remodeling that underpins the transition to OIS. Our results provide a detailed map of the chromatin landscape before cells transition to OIS thus offering a platform for manipulation of senescence outcomes of potentially therapeutic value.